Genetic modification: a tool for enhancing cellulase secretion - Anusuiya Singh; Anil Kumar Patel; Mukund Adsul; Anshu Mathur; Reeta Rani Singhania (Biofuel Research Journal, 2017)
Lignocellulosic (LC) biomass is abundantly available as a low-cost resource on the Earth. LC conversion into energy carriers is the most accepted alternative energy production policy because it is non-competitor to food or feed. LC ethanol has brought cellulases to the forefront which was otherwise lost in oblivion during last decades. LC biomass can be converted into value added products or into sugars by various routes, e.g., thermo-chemical, chemical, or biological methods. Biological route via enzymes is one of the most eco-friendly and feasible method. Both fungi and bacteria are known to degrade biomass. Fungi have been greatly exploited for cellulase production due to their inherent properties of secreting extracellular cellulase. These microorganisms are known as cellulase producers for many decades, however, to bring the enzymatic biomass conversion to an economically feasible status, extensive research efforts have been made in last decade to enhance cellulase titers. Mutations and genetic interventions along with bioprocess development have played a very important role for enhancing cellulase production. This review will present a critical overview of the on-going research towards improving cellulase production for biofuel industry via genetic modification, which will include mutation and genetic engineering employed to exert changes at genetic level in microorganisms.